Long-term Results of Duodeno-jejunal Bypass in the Treatment of Obesity and Type 2 Diabetes - Kral, Jan; Benes, Marek; Lanska, Vera; Macinga, Peter; Drastich, Pavel; Spicak, Julius; Hucl, Tomas (Obesity surgery, 2024)
PURPOSE: Obesity and its related severe comorbidities are increasing rapidly. The duodenal-jejunal bypass is an endoscopically implanted device (mimicking the Roux-en-Y gastric bypass) developed to support weight reduction and improve type 2 diabetes control. MATERIALS AND METHODS: Retrospective data analysis of consecutive patients undergoing duodenal-jejunal bypass (EndoBarrier®, DJB) implantation between 2013 and 2017 was performed to evaluate safety as well as short- and long-term efficacy. RESULTS: One hundred and twenty-one patients (mean BMI of 43.1 ± 7.2 kg/m2 and weight of 138.2 ± 28.6 kg) underwent DJB implantation. The mean dwelling time was 15.5 months, the mean total body weight loss (%TBWL) after explantation was 10.3% ± 7.9% (14.2 kg, p < 0.0001), and the mean BMI was 39.5 ± 7.3 kg/m2 (p < 0.0001). There was no significant weight gain 24 months after the explantation. Seventy-seven patients had type 2 diabetes mellitus (T2DM) with a mean HbA1c before implantation of 5.6% (n = 52). The mean HbA1c after explantation was 5.1% (p = 0.0001). Significant reductions in transaminase and lipid levels before and after explantation were observed. One complication occurred during implantation and another during explantation. In 16 patients, the device had to be extracted earlier than expected (7 for severe adverse events and 9 for adverse events; 13.2%). CONCLUSION: Despite an evident rate of adverse events, the DJB shows promise as a weight-loss procedure. Our results show that some patients implanted with the device maintained reduced weight even 24 months after explantation, while many improved T2DM control.
Keywords: výsledek terapie; Diabetes Mellitus, Type 2; Glycated Hemoglobin; Retrospective Studies; glykovaný hemoglobin; Obesity; Duodenal-jejunal bypass; lidé; Jejunum; retrospektivní studie; Weight Loss; Obesity, Morbid; obezita; žaludeční bypass; duodenum; diabetes mellitus 2. typu; hmotnostní úbytek; Treatment Outcome; Duodenum; morbidní obezita; Humans; Endoscopy; Type 2 diabetes mellitus; Gastric Bypass; Bariatric; jejunum